Pengaruh Return On Equity (ROE), Debt To Equity Ratio (DER), Investment Opportunity Set (IOS), dan Inflasi terhadap Dividend Payout Ratio (DPR) (Studi : Pada Perusahaan Property and Real Estate yang Listed di BEI Tahun 2006-2009) - Achmad Kautsar (BISMA (Bisnis dan Manajemen), 2018)
Industrial development real estate and properties in Indonesia drove the rapid post-financial crisis in 1998, indicated by increasing capacity of national property and reduced level of NPL property loans. On the other, the distribution of dividend to shareholders decreased, even many who do not share. The research was also supported by the existence of the research gap from previous studies. This study aims to examine the influence of Return On Equity (ROE), Debt to Equity Ratio (DER), Investment Opportunity Set  (IOS), and Inflation toward Dividend Payout Ratio (DPR) on property and real estate companies which listed on Indonesian Stock Exchange 2006-2009. Data sample amount of 6 companies from 41 companies those listed on Indonesian Stock Exchange. The analysis indicates that ROE variable partially significant toward DPR in property and real estate company which is listed in BEI over period 2006- 2009. While the DER, IOS and Inflation variable partially not significant toward DPR